Pourquoi certains enfants sont incomplètement vaccinés à l’âge de 2 ans ? - Boulianne, Nicole (Can J Public Health, 2003)
Objective: A survey was conducted in the Province of Quebec to document the factors associated with an incomplete immunization status among 2-year-old children. Methods: Parents of 430 completely and 266 partially vaccinated children selected from the computerized vaccination register agreed to participate. Results: The non-simultaneous administration of the 2nd MMR and 4th DPT-P-Hib at 18 months of age was responsible for 46% of incompleteness. The following characteristics were significantly associated with an incomplete immunization status: being a single parent, ≥ 2 children in the family, an older age at first immunization (≥ 3 months), parent’s preference for postponing the second vaccine when two injections are scheduled for the same visit, perception of lack of information about vaccination, and disagreement with immunization recommendations. Conclusion: One of the key points of this study is the impact of the non-simultaneous administration of the two vaccines at 18 months. Factors such as being a single parent and older age at first immunization might be used to design an early intervention for children who are most likely to be incompletely immunized. Even if parents are favourable towards immunization, they need to be well informed about the associated risks and benefits.